Synthesis of 2-Oxazolines from Ring Opening Isomerization of 3-Amido-2-Phenyl Azetidines - Xin Zhou; Baiyi Mao; Zhanbin Zhang (Molecules, 2021)
Chiral 2-oxazolines are valuable building blocks and famous ligands for asymmetric catalysis. The most common synthesis involves the reaction of an amino alcohol with a carboxylic acid. In this paper, an efficient synthesis of 2-oxazolines has been achieved via the stereospecific isomerization of 3-amido-2-phenyl azetidines. The reactions were studied in the presence of both Brønsted and Lewis acids, and Cu(OTf)2 was found to be the most effective.